Are habitat fragmentation, local adaptation and isolation‐by‐distance driving population divergence in wild rice Oryza rufipogon?. Issue 22 (5th November 2013) - Zhao, Yao; Vrieling, Klaas; Liao, Hui; Xiao, Manqiu; Zhu, Yongqing; Rong, Jun; Zhang, Wenju; Wang, Yuguo; Yang, Ji; Chen, Jiakuan; Song, Zhiping
Abstract: Habitat fragmentation weakens the connection between populations and is accompanied with isolation by distance (IBD) and local adaptation (isolation by adaptation, IBA), both leading to genetic divergence between populations. To understand the evolutionary potential of a population and to formulate proper conservation strategies, information on the roles of IBD and IBA in driving population divergence is critical. The putative ancestor of Asian cultivated rice ( Oryza sativa ) is endangered in China due to habitat loss and fragmentation. We investigated the genetic variation in 11 Chinese Oryza rufipogon populations using 79 microsatellite loci to infer the effects of habitat fragmentation, IBD and IBA on genetic structure. Historical and current gene flows were found to be rare ( m h = 0.0002–0.0013, m c = 0.007–0.029), indicating IBD and resulting in a high level of population divergence ( F ST = 0.343). High within‐population genetic variation ( H E = 0.377–0.515), relatively large effective population sizes ( N e = 96–158), absence of bottlenecks and limited gene flow were found, demonstrating little impact of recent habitat fragmentation on these populations. Eleven gene‐linked microsatellite loci were identified as outliers, indicating local adaptation. Hierarchical AMOVA and partial Mantel tests indicated that population divergence of Chinese O. rufipogon was significantly correlated with environmental factors, especially habitat temperature. Common garden trials detected a significant adaptive population divergence associated with latitude. Collectively, these findings imply that IBD due to historical rather than recent fragmentation, followed by local adaptation, has driven population divergence in O. rufipogon .